2017
DOI: 10.1097/j.pain.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and costs of a vocational advice service to improve work outcomes in patients with musculoskeletal pain in primary care: a cluster randomised trial (SWAP trial ISRCTN 52269669)

Abstract: Musculoskeletal pain is a common cause of work absence, and early intervention is advocated to prevent the adverse health and economic consequences of longer-term absence. This cluster randomised controlled trial investigated the effect of introducing a vocational advice service into primary care to provide occupational support. Six general practices were randomised; patients were eligible if they were consulting their general practitioner with musculoskeletal pain and were employed and struggling at work or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“… 16 The SWAP study found that a vocational advice service in primary care was successful in improving work ability for patients with musculoskeletal pain. 54 “Convergence Dialogue Meetings” (CDMs) were developed in Sweden for patients on sick leave due to burnout. 29 The CDM model is a 3-step structured interview model where the patient, the health care provider, and the employer meet for shared discussions on concrete suggestions and actions to support sustainable work ability and, when applicable, return-to-work.…”
Section: Introductionmentioning
confidence: 99%
“… 16 The SWAP study found that a vocational advice service in primary care was successful in improving work ability for patients with musculoskeletal pain. 54 “Convergence Dialogue Meetings” (CDMs) were developed in Sweden for patients on sick leave due to burnout. 29 The CDM model is a 3-step structured interview model where the patient, the health care provider, and the employer meet for shared discussions on concrete suggestions and actions to support sustainable work ability and, when applicable, return-to-work.…”
Section: Introductionmentioning
confidence: 99%
“…The SWAP trial was therefore the first to provide an early VAI, embedded in UK general practice, to people with musculoskeletal pain, a leading cause of work absence. The results of the trials showed that the VAI significantly reduced days absent over 4 months and was cost effective compared to best care [ 16 ], however, exploratory subgroup analysis in those participants with < 10 days absence versus ≥ 10 days but < 6 months absent at baseline found that the intervention was more successful in those with the longer absence duration. These results suggest that a VAI might be better targeted to those with > 10 days (2 working weeks) of absence.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this intervention has not yet been tested in other settings or countries the publication of the development and content of the VAI means that it can more easily be tested for generalisability. Full results of the SWAP randomised trial, which tested the VAI, have recently been published [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations